Sintegritas Advokat di Indonesia Dalam Pemberian bantuan Hukum secara Cuma-Cuma (Prodeo) - Aina Fazira; Melisa Siregar; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
In carrying out their responsibilities, advocates must be honest, have a strong character, and of course have high intelligence. In addition, advocates must have determination because that is even more important than their skills or vision for the cause. anybody. As a result, Article 28D paragraph (1) of the 1945 Constitution stipulates that "everything related to the protection of dignity is further regulated". Everyone has the right to be recognized, protected, to receive fair legal certainty and to be treated equally before the law. In accordance with human dignity, Article 34 paragraph 2 of the 1945 Constitution states that the state creates a social security system for all people and empowers the weak and incapable. Laws and regulations are based on the 1945 Constitution, one of which is Law Number 16 of 2011 concerning Legal Aid. In accordance with Law no. 16 of 2011, the idea that the state is responsible for providing legal assistance to the poor as a means of ensuring access to justice is the basis for consideration for passing this law. Keywords: Advocate, Sintergrity, Prodeo